Green Accounting, Green Innovation, and Emission Carbon Disclosure: A Literature Study - Afifah; Febrianti, Intan; Suci Amal; Said, Darwis; Damayanti, Ratna Ayu; Syarifuddin (MultiTech Publisher, 2024)
Literature studies regarding Green Accounting, Green Innovation, and Carbon Emission Disclosure show that companies must pay attention to environmental impacts in their operational activities. A focus on economic and environmental sustainability is important for companies, especially with increasing concerns about environmental impacts. Green Accounting is the process of managing environmental costs to support management decisions. Green Innovation, as an important part of environmental protection, can change consumer lifestyles and encourage sustainable behavior. Carbon Emission Disclosure plays a role in validating a company's efforts to reduce carbon emissions The results of previous research show that Green Accounting has a positive effect on company sustainability performance, especially in waste management. Green Innovation can improve a company's ESG performance, while Carbon Emission Disclosure helps in reducing carbon emissions and disclosing information to stakeholders Overall, this article provides an in-depth understanding of the importance of Green Accounting, Green Innovation, and Carbon Emission Disclosure in maintaining a company's environmental and social sustainability. By paying attention to environmental impacts in business activities, companies can improve their performance in a sustainable manner